Investitionen und Regulierung bei schnellen Internetzugängen in Deutschland und der Schweiz - Georg Götz; Patrick Zenhäusern (Wirtschaftsdienst, 2013)
Schnellen Breitbandzugängen für möglichst viele Haushalte wird eine große Bedeutung zugemessen. Die dafür notwendige Technik erfordert allerdings relativ hohe Investitionen. Die EU und mit ihr auch Deutschland sowie die Schweiz verfolgen unterschiedliche Regulierungsregime, wobei die Schweiz offensichtlich bessere Ergebnisse erreicht. – – The transition from copper-based internet access to ultra-fast broadband networks requires large investments. However, regulation has a serious impact on (private) investment incentives. We describe and evaluate the regulatory frameworks of European countries, in particular those of Germany and Switzerland. Our article argues that the ex-ante sector-specifi c regulation in EU countries like Germany, with its focus on cost-oriented access and service-based competition, is likely to have a detrimental effect on investment. In contrast, the Swiss approach of ex-post regulation provides a more conducive investment environment. We provide preliminary evidence on investment behaviour supporting our theoretical conclusions.
Keywords: L51; L96; 330; Internet; Netzzugang; Breitbandkommunikation; Telekommunikationspolitik; Vergleich; Deutschland; Schweiz